The Effect of Tax Sanctions, Modern Tax Administration System, E-Filing and Tax Volunteers on Taxpayer Compliance - Indrawan, Andri; Suherman, Acep; Damayanti, Conny (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This study aims to analyze the factors that influence taxpayer compliance. By using empirical data and case studies By analyzing the influence of tax sanctions, modern tax administration systems, e-filing and tax volunteers on taxpayer compliance. The method in this study is a type of research that uses associative quantitative research methods and sampling techniques, namely random sampling on UMKM taxpayers registered at the Sukabumi Pratama Tax Office. To determine the size of the sample in this study, the Slovin formula was used in its calculations and 100 samples were obtained. Based on the results of statistical tests that tax sanctions and modern tax systems do not affect taxpayer compliance and the results of statistical tests show that E-filing, tax volunteers have a positive effect on taxpayer compliance. The taxpayer compliance variable can be explained by the E-filing and tax volunteers variables by 33.6%. The remaining 66.4% is influenced by other factors not examined in this study, such as tax knowledge, taxpayer awareness, education level, and other factors that have the potential to influence taxpayer compliance.